2013
DOI: 10.1093/jxb/ert351
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic stress-induced polyamine oxidation mediates defence responses and reduces stress-enhanced grapevine susceptibility to Botrytis cinerea

Abstract: Abiotic factors inducing osmotic stress can influence the plant immune response and resistance to pathogen infections. In this study, the effect of polyethylene glycol (PEG)- and sucrose-induced osmotic stress on polyamine (PA) homeostasis and the basal immune response in grapevine plantlets before and after Botrytis cinerea infection was determined. Pharmacological approaches were also addressed to assess the contribution of osmotic stress-induced PA oxidation to the regulation of defence responses and the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…PA oxidation has been associated with stress-induced phenylpropanoid metabolism in cell cultures of the grape vine (Vitis vinifera L. -Hatmi et al 2014). PA oxidation releases H2O2, which promotes cell-wall stiffening through formation of covalent cross links between cell wall components (Pottosin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…PA oxidation has been associated with stress-induced phenylpropanoid metabolism in cell cultures of the grape vine (Vitis vinifera L. -Hatmi et al 2014). PA oxidation releases H2O2, which promotes cell-wall stiffening through formation of covalent cross links between cell wall components (Pottosin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to Deluc et al (2011), water deficit induced the levels of tpiceid in Cabernet Sauvignon berries but not in Chardonnay. Hatmi et al (2014) found that osmotic stress induced by PEG and sucrose increased the accumulation of tresveratrol and e-viniferin in the leaves of V. vinifera cv. Chardonnay.…”
Section: Biotic and Abiotic Stresses As Regulators Of Stilbene Biosynmentioning
confidence: 97%
“…In proembryogenic cells (i.e., the cells not yet induced to maturation), the content of secondary metabolites is generally low (Vuosku et al 2012). However, osmotic stress has been found to induce secondary metabolism also in the proembryogenic cell cultures (Cvikrová et al 2008;Hatmi et al 2014) and can be related to, i.e., cell wall stiffening (Boudet 2007). Phenylalanine ammonia lyase (PAL) links primary and secondary metabolism by catalyzing the conversion of L-phenylalanine to cinnamic acid, the initial substrate of phenylpropanoid metabolism (Butland et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The content of hydroxycinnamic acid was decreased by PAL inhibitor in alfalfa (Medicago sativa) suspension cultures, which influenced the balance of free and conjugated PA contents and stimulated cell division activity (Cvikrová et al 1999). Moreover, in grape vine (Vitis vinifera L.) subjected to osmotic stress, PA homeostasis was recently linked with parallel accumulation of main stilbenes and up-regulation of gene transcripts including stilbene synthases (STS) (Hatmi et al 2014). psSTS of Scots pine has been characterized as a dihydropinosylvinsynthase (Fliegmann et al 1992), and psSTS catalyzes biosynthesis of the stilbene backbone from malnoyl-CoA and one CoA-ester of cinnamic acid derivative (Chong et al 2009) (see the figure Online Resource 2).…”
Section: Introductionmentioning
confidence: 99%